Development of New Therapeutics to Meet the Current Challenge of Drug Resistant Tuberculosis - Sheikh, Bashir A; Bhat, Basharat A; Mehraj, Umar; Mir, Wajahat; Hamadani, Suhail; Mir, Manzoor A (Current pharmaceutical biotechnology, 2021)
Tuberculosis (TB) is a prominent infective disease and a major reason of mortality/ morbidity globally. Mycobacterium tuberculosis causes a long-lasting latent infection in a significant proportion of human population. The increasing burden of tuberculosis is mainly caused due to multi drug-resistance. The failure of conventional treatment has been observed in large number of cases. Drugs that are used to treat extensively drug-resistant tuberculosis are expensive, have limited efficacy, and have more side effects for a longer duration of time and are often associated with poor prognosis. To regulate the emergence of multidrug resistant tuberculosis, extensively drug-resistant tuberculosis and totally drug resistant tuberculosis, efforts are being made to understand the genetic/molecular basis of target drug delivery and mechanisms of drug resistance. Understanding the molecular approaches and pathology of Mycobacterium tuberculosis through whole genome sequencing may further help in the improvement of new therapeutics to meet the current challenge of global health. Understanding cellular mechanisms that trigger resistance to Mycobacterium tuberculosis infection may expose immune associates of protection, which could be an important way for vaccine development, diagnostics, and novel host-directed therapeutic strategies. The recent development of new drugs and combinational therapies for drug-resistant tuberculosis through major collaboration between industry, donors, and academia gives an improved hope to overcome the challenges in tuberculosis treatment. In this review article, an attempt was made to highlight the new developments of drug resistance to the conventional drugs and the recent progress in the development of new therapeutics for the treatment of drugresistant and non-resistant cases.